The correlation between high-sensitivity cardiac troponin levels in diabetic patients’ serum and lower limb lesions: based on NHANES data - Li, Lin; Jiao, Linxi; Yang, Danyang; Zhao, Jingxia; Li, Ping (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the association of hypersensitive cardiac troponin (hs-cTnT), a biomarker of myocardial injury, with diabetic lower extremity disease in American adults.MethodsWe conducted a cross-sectional study (unweighted N=1,196) of diabetic patients aged 40 years or older who participated in the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2004. Logistic regression was used to assess the association of hs-cTnT with lower extremity disease, including peripheral neuropathy (as assessed by monofilament test), peripheral artery disease (as assessed by ankle-brachial index), history of foot ulcers, or amputation. All analyses are weighted.ResultsThe prevalence rate of diabetic lower extremity disease was 41.6%. Adjusted hs-cTnT was significantly associated with lower limb disease in adults with diabetes. There is interaction between chronic kidney disease and hs-cTnT, which strongly interferes with the correlation between hs-cTnT and lower extremity lesions in diabetic patients.ConclusionsOur study suggests the usefulness of hs-cTnT as a biomarker for lower extremity lesions in adults with diabetes and highlights the potential direct interaction of hs-cTnT with chronic kidney disease.